2015
DOI: 10.1016/j.tpb.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Long-range dispersal, stochasticity and the broken accelerating wave of advance

Abstract: Rare long distance dispersal events are thought to have a disproportionate impact on the spread of invasive species. Modelling using integrodifference equations suggests that, when long distance contacts are represented by a fat-tailed dispersal kernel, an accelerating wave of advance can ensue. Invasions spreading in this manner could have particularly dramatic effects. Recently, various authors have suggested that demographic stochasticity disrupts wave acceleration. Integrodifference models have been widely… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
(190 reference statements)
1
4
0
Order By: Relevance
“…(6.6) diverge for all z. This is analytic confirmation of the observations of Jacobs and Sluckin [2015] that Cauchy kernels lead to accelerating invasions, even in the presence of density-dependence.…”
Section: Setssupporting
confidence: 82%
See 2 more Smart Citations
“…(6.6) diverge for all z. This is analytic confirmation of the observations of Jacobs and Sluckin [2015] that Cauchy kernels lead to accelerating invasions, even in the presence of density-dependence.…”
Section: Setssupporting
confidence: 82%
“…For the case of density-independent proliferation, invasions accelerate faster than geometrically [Kot et al, 1996]. Méndez et al [2010] predicted and Jacobs and Sluckin [2015] observed numerically that invasions with carrying capacities exhibited finite speeds as long as β > 3, but that infinite speeds appeared when β < 3, even in systems with hard carrying capacities. The subsequent analysis provides further explanation.…”
Section: Power-law Tailsmentioning
confidence: 96%
See 1 more Smart Citation
“…The underlying process of long-distance dispersal in a finite-size population is inherently stochastic, which may result in the inaccuracy of deterministic models when long-distance dispersal is frequent [ 30 , 41 ]. Ralph and Coop [ 22 ] show that under some conditions, properties of a stochastic traveling wave can be approximated well by considering a single “mean” wave that is representative of the wave’s path (their work in this area arises in the case of multiple adaptive lineages and is further described in the next section).…”
Section: Population Genetic Models For the Spatial Spread Of Advantag...mentioning
confidence: 99%
“…A similar approach, space-fractional diffusion, arises from a generalization of a random walk when the distribution of step sizes in the walk is described by a power law, x −(1+α) with α ≤ 2, rather than a Gaussian function of the step sizes. This type of model has general application across fields from plasma physics [12] to ecology [13,14]. Mathematically, this heavy-tailed distribution of step sizes with an infinite variance produces superdiffusive dispersion, also known as a Lévy flight.…”
Section: Introductionmentioning
confidence: 99%